(untitled) (KYAMC Journal, 2013)
Genital infections by Chlamydia trachomatis are now recognized as highly prevalent sexually transmissible disease. In frequency, they surpass the classic sexually transmissible diseases such as syphilis and gonorrhea and thus constitute a serious public health problem. Chlamydia trachomatis is an obligate intracellular gram negative bacterium which have a unique growth cycle and are placed in their own family (Chlamydiae).Chlamydia trachomatis is now one of the most Prevalent bacteria found in classic sexually transmissible disease and as such constitutes a serious Public heath problem. World Heath Organization (WHO) estimated that 92 million new chlamydial infections occur worldwide annually affecting more women (50 Million) then men (42million). And highest chlamydial infected population were in south and South-east Asia (43million) then sub- Saharan Africa (16million)(WHO 2001).This review article is a discussion on history,epidemiology, pathogenesis, clinical features, diagnosis and modern trend of treatment, prevention of Chlamydial infections in age group. Effective delivery of prevention messages requires clientcentered counseling and education regarding specific actions that can reduce the risk for chlamydia transmission e.g., abstinence, condom use, limiting the number of sex partners,modifying sexual behaviors and vaccination. DOI: http://dx.doi.org/10.3329/kyamcj.v3i1.13660 KYAMC Journal Vol. 3, No.-1, June 2012 pp.244-249